Is Anywhere Stuck in a Malthusian Trap? - Kenny, Charles (2012)
The key features of the Malthusian model are that (i) income determines population growth, with rising wages increasing survival rates and (ii) there is a vital factor of production (land) which is fixed, implying decreased returns to scale for all other factors. The equilibrium state in such a model is a population living on subsistence incomes. The country-level analysis in this paper suggests that (i) the link between income and population growth is (almost) everywhere broken and (ii) there is little evidence of declining returns to scale because of constraints imposed by land carrying capacity anywhere. Population dynamics are being driven by non-income factors in a manner that is reducing population growth rates everywhere. At the same time, output is increasing everywhere, in a manner inconsistent with significantly declining returns to scale based on land being a vital factor of production.